Effectiveness of Intradialytic Exercise on Fatigue in Chronic Kidney Failure Patients Undergoing Hemodialysis Therapy - Safruddin Safruddin; Rizki Nugraha Agung; Dewi Anggraini; Wati Jumaiyah (Indonesian Journal of Global Health Research, 2025)
Fatigue is one of the most common symptoms experienced by patients undergoing hemodialysis therapy. This condition can affect the quality of life of chronic patients, because reduced physical activity, such as sedentary habits, and emotional stress can also be the cause of fatigue. Intradialitic exercise has various benefits in reducing fatigue experienced by patients. This study aims to evaluate the effect of exercise training on the level of fatigue in patients undergoing hemodialysis therapy. The study used a design Quasi-experimental research using the pre-test and post test group design. The research population was all patients with end-stage renal failure with the sampling technique being accidental sampling, with amount sample of 22 patients. Intradialytic exercises were performed for six weeks at a frequency of twice a week, with each session lasting a maximum of 20 minutes. Fatigue levels were measured using the Functional Assessment of Chronic Illness Therapy (FACIT) questionnaire. Data analysis was performed using the dependent t-test. The results of the study showed that the average level of fatigue before the intervention is 26.36 (SD ± 3.580 ), while the average score is the fatigue level after intervention is 32.09 (SD ±4.116 ) with a p value of 0.001, the effect size is -3.378, then including in category effect tall based on Cohen'. There is significant difference between fatigue levels before and after interdialytic exercise in patients with chronic renal failure undergoing hemodialytic therapy.